Law of intellectual property rights - Avadhani, V. S. R. (Hyderabad)
Intellectual Property (IP) is the creation of human intellect. It refers to the ideas, knowledge, invention, innovation, creativity, and research etc, all being the product of human mind and is similar to any property, whether movable or immovable, wherein the proprietor or the owner may exclusively use his property at will and has the right to prevent
Keywords: Intellectual property rights-law